Optimizing customer experience through omnichannel marketing in retail companies during the digital transformation era - Izharuddin Pagala; Reina A. Hadikusumo; Andriya Risdwiyanto; Scherly Hansopaheluwakan; Dita Rosyalita (Jurnal Indovisi, 2026)
The rapid advancement of digital transformation has significantly changed customer behavior and challenged retail companies to deliver seamless experiences across multiple channels. This study aims to examine the role of omnichannel marketing in optimizing customer experience within retail companies during the digital transformation era. The research employs a library research approach, utilizing primary and secondary data collected from books, academic journals, research reports, and other relevant scientific publications. Data were analyzed using content analysis to identify patterns, relationships, and key insights regarding omnichannel marketing, customer experience, and digital transformation. The findings indicate that omnichannel marketing enhances customer experience through the integration of online and offline channels, personalized interactions, service consistency, and effective utilization of digital technologies. Furthermore, the study reveals that customer satisfaction, engagement, trust, and loyalty are positively influenced by seamless omnichannel experiences. Despite challenges related to technological complexity and organizational readiness, omnichannel marketing remains a critical strategy for improving competitiveness and sustaining long-term customer relationships. The study concludes that customer-centric omnichannel implementation is essential for retail success in the digital transformation era.